Intravitreal Aflibercept as a Rescue Therapy for Retinal Neovascularization and Macular Edema due to Eales Disease. (11th February 2021) - Hsia, Ning-Yi; Lin, Chun-Ju; Lai, Chun-Ting; Bair, Henry; Chang, Cheng-Hsien; Lin, Jane-Ming; Tsai, Yi-Yu
Abstract : We report the rescue effect of intravitreal aflibercept injections on retinal neovascularization and macular edema due to Eales disease. Case 1 was a 36-year-old female. Intravitreal aflibercept was administered as rescue therapy after persistent retinal neovascularization following retinal photocoagulation, periocular triamcinolone, and intravitreal ranibizumab injection. Retinal neovascularization initially regressed, but recurred after 5 months along with macular edema. Two more intravitreal aflibercept injections were given, and retinal neovascularization with macular edema regressed. Her vision improved to 20/25 and remained stable after 43 months. Case 2 was a 27-year-old female. Intravitreal aflibercept was administered after persistent retinal neovascularization and macular edema following periocular triamcinolone injection. The macular edema initially subsided but recurred after 3 months. Intravitreal aflibercept injections were then administered once every three months to maintain her vision 20/20. The patient has been followed up for 28 months. Intravitreal aflibercept was effective as a rescue therapy in the treatment of Eales disease to regress retinal neovascularization, though repeated injections were necessary in cases of recurrence.